2015
DOI: 10.1089/ars.2013.5778
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Treatments of Oxidative Injury in Ischemic Stroke: Focus on the Phagocytic NADPH Oxidase 2

Abstract: Radical scavenger compounds (such as Ebselen and Edaravone) are under clinical investigation as a therapeutic approach against stroke. On the other hand, NOX inhibition might represent a promising strategy to prevent the stroke-related injury. Although selective NOX inhibitors are not yet available, nonselective compounds (such as apocynin and fasudil) provided encouraging results in preclinical studies. Whereas additional studies are needed to better evaluate this therapeutic potential in human beings, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 242 publications
(204 reference statements)
2
42
0
Order By: Relevance
“…The discrepancy could be related to the length of ischemia as the MCAO lasted less than 2 h in previous studies 11 26. The association of NOX2 and NOX4 with cerebral ischemia/reperfusion injury and hemorrhage is consistent with the results of NOX2 or NOX4 knockout studies 13 25. Treatment with NOX2/4 inhibitor VAS2870 not only reduced mechanical reperfusion-induced hemorrhage and infarct size but also suppressed the upregulation of NOX2 and NOX4.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The discrepancy could be related to the length of ischemia as the MCAO lasted less than 2 h in previous studies 11 26. The association of NOX2 and NOX4 with cerebral ischemia/reperfusion injury and hemorrhage is consistent with the results of NOX2 or NOX4 knockout studies 13 25. Treatment with NOX2/4 inhibitor VAS2870 not only reduced mechanical reperfusion-induced hemorrhage and infarct size but also suppressed the upregulation of NOX2 and NOX4.…”
Section: Discussionsupporting
confidence: 66%
“…It is thus plausible that ischemic reperfusion upregulated NOX2 and NOX4, which in turn resulted in the overproduction of ROS. ROS triggered a series of biological responses leading to disruption of the BBB and augmented apoptosis 12 13 25. Inhibition of the NOX pathway may thus be a potential treatment target to improve outcome in patients undergoing mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This redox unbalance triggers early inflammatory responses, involving both microglial and neuronal cells, as well as circulating leukocytes (Figure 3) [80]. ROS are essential mediators in the inflammatory environment whose major source is nicotinamide adenine dinucleotide phosphate hydrogen oxidase (NOX) [81] together with immune cells infiltrating ischemic tissue [82].…”
Section: Soluble Mediators Of Post-ischemic Brain Injurymentioning
confidence: 99%
“…Studies using neutrophils of X-CGD patients and NOX2 KO mice demonstrated that neutrophil NOX2-generated ROS are crucial for killing microbial pathogens [187, 188] and function as signaling molecules that regulate the activity of kinases and phosphatases [189]. Despite the importance of NOXs-generated ROS for thromboin-flammation including ischemic stroke [190, 191], it remains poorly understood how ROS mechanistically contribute to the pathogenesis.…”
Section: Molecules Regulating the Function Of Surface Receptors Requimentioning
confidence: 99%